THE ORAL APPROACH AND SITUATIONAL LANGUAGE TEACHING - Ibodullayeva, Mohinur Ziyodullo qizi; Shodiev , Ibrohim Madjidovich (INTERNATIONAL CONFERENCE DEDICATED TO THE ROLE AND IMPORTANCE OF INNOVATIVE EDUCATION IN THE 21ST CENTURY, 2022)
This article considers the Oral Approach and situational language teaching, and how the Oral Approach relies on the use of situations to teach language.